Pengaruh Debt To Equity Ratio, Return On Equity, Return On Assets Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Farmasi - Jufrizen Jufrizen; Illa Nurain Al Fatin (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
The purpose of this study was to determine and analyze the influence of Debt to Equity Ratio, Return On Equity, Return On Assets and firm size on firm value either partially or simultaneously on Pharmaceutical Companies Listed on the Indonesia Stock Exchange. The approach used in this research is an associative approach. The population in this study are all pharmaceutical companies that are listed on the Indonesia Stock Exchange while the samples that meet the criteria for withdrawal of observations made for five years and as many as six (6) pharmaceutical companies listed on the Indonesia Stock Exchange. Data collection techniques in this study using documentation techniques. Data analysis techniques in this study used the Multiple Regression. The results of this study prove that partially there is no influence of Debt to Equity Ratio on firm value. there is no effect of Return On Equity on firm value, there is no effect of Return On Assets on firm value, there is no influence of firm value on firm value. Simultaneously there is no influence of Debt to Equity Ratio, Return On Equity, Return On Assets and firm size together on the firm value of pharmaceutical companies listed on the Indonesia Stock Exchange